Post-operative Carcinoembryonic Antigen (CEA) Increase as an Indicator of Recurrence After Resection in Colorectal Cancer Patients at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar - Cokorda Bagus Nurparma Putra; Made Agus Dwianthara Sueta; Ketut Sudartana (Epidemiology and Society Health Review (ESHR), 2026)
Background: Carcinoembryonic Antigen (CEA) is a glycoprotein utilised as a serological marker for postoperative surveillance of colorectal cancer. Its role in predicting recurrence after curative resection remains a subject of debate.This study aimed to evaluate post-operative CEA as an indicator and predictor of recurrence after resection in colorectal cancer patients, and to determine the disease-free survival (DFS) over 24 months. Methods: A retrospective cohort study was conducted at the Digestive Surgery Outpatient Clinic of Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, Bali, from December 2024 to February 2025. A total of 66 patients with stage II–III colorectal cancer who had undergone curative resection (R0) between 2018 and 2022 were enrolled. Post-operative CEA was measured at a minimum of four months after resection. Patients were followed for recurrence and disease-free survival over a 2-year period. Results: Of 66 patients, 43 (65.2%) experienced recurrence. Post-operative CEA >5 ng/mL was significantly associated with recurrence (RR = 1.82; 95% CI: 1.357–2.444; p = 0.001). ROC curve analysis identified an optimal CEA fluctuation cut-off of 1.01 ng/mL as a “surveillance threshold” for predicting recurrence (AUC = 0.821; sensitivity 72.1%; specificity 95.7%). The optimal post-operative CEA cut-off was 4.11 ng/mL (AUC = 0.696; p = 0.009). Two-year DFS was significantly lower in patients with post-operative CEA >4.11 ng/mL versus those with CEA ≤4.11 ng/mL (40% vs. 63%; p = 0.001). Conclusion: Elevated post-operative CEA was significantly associated with recurrence after resection in colorectal cancer patients. A CEA increase of 1.01 ng/mL can serve as a “surveillance threshold” to indicate possible recurrence. CEA should be combined with radiological imaging for optimal surveillance.